Improving Students’ Academic Achievement in Biology, Using Information and Communication Technology Aided Instruction - Adebanjo, Adedoyin A. (NIU Journal of Social Sciences; Vol 5 No 4 (2019): KIU Journal of Social Sciences, Vol. 5 No. 4, December 2019, 2020)
Information and communication technologies (ICT) have changed the pedagogy in education from teacher-centered approach to student-centered approach and also enhance teaching and learning. The purpose of this study was to investigate how students’ academic achievement in Biology can be improved using information and communication technology aided instruction . The moderating effect of gender was also examined. The study adapted pre-test, post-test, control group quasi-experimental design, involving 2x2 factorial matrix. The sample consisted of sixty four (64) SS 2 students offering Biology selected using purposive sampling technique from two out of thirty six schools in Sagamu Local Government Area of Ogun State. Randomization was used to place the schools into experimental and control groups. The experimental group was taught using ICT aided instruction powered by computer applications and while conventional method was used for control group. Three hypotheses were formulated and tested at 0.05 level of significance. A validated Biology Achievement Test (r=0.67) was used to measure students’ achievement in Biology. Data were analyzed inferentially by analysis of covariance (ANCOVA) and also multiple classification analysis (MCA) was used to explain the magnitude of the mean post test achievement scores across the different levels of instructional strategy and gender. Findings indicated that there was significant effect of ICT aided instruction on students’ achievement in Biology (F (1,59) =183.103, P< 0.05). However, no significant main effect of gender was found on students’ achievement in Biology (F (1,59) = 0.052, P>0.05). No significant 2-way interaction effect of gender was found in students’ achievement in Biology (F (1,59) = 0.190, P>0.05). In view of the findings, it was recommended that government should provide ICT resources to secondary schools in Nigeria and also educational authorities should lay more emphasis on modern educational resources that promote effectiveness in teaching and learning process. Keywords: Information and Communication Technology, ICT- aided Instruction, Students’ Academic Achievement, Gender, Achievement in Biology